TRANSESTERIFIKASI MINYAK DEDAK PADI SECARA IN-SITU DENGAN BANTUAN GELOMBANG MIKRO - Rahkadima, Yulia Tri; A’yuni, Qurrota (Universitas Nahdlatul Ulama Sidoarjo, 2017)
Rice bran as rice milling waste is very promising to be used as raw material of oil producer such as biodiesel oil. The production process with the assistant of microwaves has been studied in this research. The production process was carried out in-situ where the extraction process of rice bran oil and the biodiesel formation reaction occur simultaneously in microwave radiation. Rice bran was obtained from Lamongan area with IR 64 type. The reaction was carried out in microwaves that had been modified by variation of operating conditions including reaction times (10, 30 and 50 min) and weight ratio of rice bran to methanol (1:4, 1:8, 1:12, 1:16 and 1:20). The results obtained are then analyzed by product yield and free fatty acid content. The optimum condition is obtained when the highest yield of the product with the lowest free fatty acid. The results showed that the optimum condition was obtained at reaction time of 30 minutes with the ratio of rice bran: methanol at 1:12.